Psychosocial climate and labor welfare in a hospital of category II in Tarma, Peru - Castañeda-Miguel, Suset M. (2024)
Objective. Determine the relationship between the climate psychosocial and the welfare labor in a hospital of category II of a region of Peru. Materials and methods. The research used the method quantitative, it was of type basic and level correlational, being realized with a design cross-sectional non-experimental. Is counted with a population of 80 people and a sample of 67, among the workers of the Hospital Felix Mayorca Soto. The instrument employed was a questionnaire using the scale of Likert, with coefficient of reliability alpha of Cronbach's of 0.98 and 0.79, respectively. Results. To according to the results obtained, there exists a correlation minimum of statistics significant with a p-value of 0.000072, being favorable the strength correlational. Conclusions. In the environment of job, it is visualized that the state of the climate psychosocial and the welfare labor of the collaborators influence the one onto the other, seeking the welfare general of the staff administrative; so that to better climate psychosocial also there will be an improvement in the welfare labor.